2020
DOI: 10.1002/jcla.23423
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: A landscape of circulating long non‐coding RNA (lncRNA) expression profile and the predictive value of candidate lncRNAs for disease risk of knee osteoarthritis

Abstract: Background This study aimed to investigate the plasma long non‐coding RNA (lncRNA) expression profile in knee osteoarthritis (KOA) patients and the value of candidate lncRNAs for predicting KOA risk. Methods Plasma was obtained for RNA sequencing (RNA‐seq) in eight KOA patients and eight healthy controls (Ctrls). Ten candidate lncRNAs were then selected from the differentially expressed (DE) lncRNAs according to the rank of absolute value of Log2 (fold change). Afterward, RT‐qPCR was used to examine 10 candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 31 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…L ncRNA is an RNA molecule with a length of more than 200 nucleotides and is a by-product of RNA polymerase 73 Even some lncRNA are considered to be biomarkers that distinguish osteoarthritis from healthy people and disease progression. They found that eight lncRNA had the value of predicting KOA risk, and six candidate lncRNA could independently predict KOA risk.…”
Section: Proteinasementioning
confidence: 99%
See 4 more Smart Citations
“…L ncRNA is an RNA molecule with a length of more than 200 nucleotides and is a by-product of RNA polymerase 73 Even some lncRNA are considered to be biomarkers that distinguish osteoarthritis from healthy people and disease progression. They found that eight lncRNA had the value of predicting KOA risk, and six candidate lncRNA could independently predict KOA risk.…”
Section: Proteinasementioning
confidence: 99%
“…Liu et al found 418 up‐regulated lncRNA and 347 down‐regulated lncRNA in KOA patients. Enrichment analysis found that DE lncRNA was mainly enriched in biological processes, molecular functions, and signaling pathways related to inflammation and bone formation 73 . Even some lncRNA are considered to be biomarkers that distinguish osteoarthritis from healthy people and disease progression.…”
Section: Long Non‐coding Rna(lncrna)mentioning
confidence: 99%
See 3 more Smart Citations